1998
DOI: 10.1172/jci2169
|View full text |Cite
|
Sign up to set email alerts
|

Caspase inhibitor affords neuroprotection with delayed administration in a rat model of neonatal hypoxic-ischemic brain injury.

Abstract: Programmed cell death (apoptosis) is a normal process in the developing nervous system. Recent data suggest that certain features seen in the process of programmed cell death may be favored in the developing versus the adult brain in response to different brain injuries. In a well characterized model of neonatal hypoxia-ischemia, we demonstrate marked but delayed cell death in which there is prominent DNA laddering, TUNEL-labeling, and nuclei with condensed chromatin. Caspase activation, which is required in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
365
5
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(404 citation statements)
references
References 45 publications
32
365
5
2
Order By: Relevance
“…Recent studies have also provided additional evidence of caspase-3 activation in other models of cerebral ischemia following strokes in adults and neonates. This includes the mitochondrial release of cytochrome c and activation of caspase-9, a proximal caspase in the caspase-3 apoptotic cascade (Gillardon et al, 1997;Cheng et al, 1998;Namura et al, 1998;Pulera et al, 1998;Kiprianova et al, 1999;Krajewski et al, 1999;Ouyang et al, 1999;Velier et al, 1999;. Several recent studies using caspase inhibitors provide support of these original observations, and demonstrate that injury severity can affect the efficacy of caspase inhibitors in reducing cell death.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 89%
“…Recent studies have also provided additional evidence of caspase-3 activation in other models of cerebral ischemia following strokes in adults and neonates. This includes the mitochondrial release of cytochrome c and activation of caspase-9, a proximal caspase in the caspase-3 apoptotic cascade (Gillardon et al, 1997;Cheng et al, 1998;Namura et al, 1998;Pulera et al, 1998;Kiprianova et al, 1999;Krajewski et al, 1999;Ouyang et al, 1999;Velier et al, 1999;. Several recent studies using caspase inhibitors provide support of these original observations, and demonstrate that injury severity can affect the efficacy of caspase inhibitors in reducing cell death.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 89%
“…Z-VAD-FMK, a pancaspase inhibitor (36)(37)(38)(39)(40)(41)(42), can inhibit cell death in response to mechanical injury. Interestingly, our results showed that Z-VAD-FMK could inhibit chondrocyte death more effectively in chondroitinase ABC-treated explants than in control explants.…”
Section: Discussionmentioning
confidence: 99%
“…Because inhibition of apoptosis, IL-6, or P-selectin has been demonstrated to protect against I/R-induced organ failure in the kidney, 15,[22][23][24] heart, 35,36 brain, 37,38 intestine, 39 and liver, 40 GC-G may also be involved in I/R-induced abnormalities in other organs, such as acute myocardial infarction in the heart or stroke in the brain, which warrants further investigation. Although the exact mechanism by which GC-G is regulated under renal I/R remains undefined, a simple regulatory mechanism could be that renal I/R induces the release of endogenous ligand(s) and modulates GC-G activity to transmit the injury signal leading to apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%